2021
DOI: 10.3389/fgene.2021.683939
|View full text |Cite
|
Sign up to set email alerts
|

Expression Profiling and Functional Analysis of Candidate Col10a1 Regulators Identified by the TRAP Program

Abstract: Hypertrophic chondrocytes and their specific marker, the type X collagen gene (Col10a1), are critical components of endochondral bone formation during skeletal development. We previously found that Runx2 is an indispensable mouse Col10a1 gene regulator and identified many other transcription factors (TFs) that potentially interact with the 150-bp Col10a1 cis-enhancer. However, the roles of these candidate TFs in Col10a1 expression and chondrocyte hypertrophy have not been elucidated. Here, we focus on 32 candi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 59 publications
2
6
0
Order By: Relevance
“…To investigate the underlying mechanism of Dlx5 's up-regulation of Col10a1 , we analyzed the binding sites within the 150-bp Col10a1 cis-enhancer using JASPAR software. 19 The result confirmed the existence of the DLX5 binding site as previously identified by the TRAP program. 19 Importantly, we demonstrate that such DLX5 binding site is functional as evidenced by the results of the dual-luciferase reporter and ChIP assays, as well as the results of the co-transfection studies.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…To investigate the underlying mechanism of Dlx5 's up-regulation of Col10a1 , we analyzed the binding sites within the 150-bp Col10a1 cis-enhancer using JASPAR software. 19 The result confirmed the existence of the DLX5 binding site as previously identified by the TRAP program. 19 Importantly, we demonstrate that such DLX5 binding site is functional as evidenced by the results of the dual-luciferase reporter and ChIP assays, as well as the results of the co-transfection studies.…”
Section: Discussionsupporting
confidence: 86%
“… 19 The result confirmed the existence of the DLX5 binding site as previously identified by the TRAP program. 19 Importantly, we demonstrate that such DLX5 binding site is functional as evidenced by the results of the dual-luciferase reporter and ChIP assays, as well as the results of the co-transfection studies. Not surprisingly, the functional DLX5 binding site is adjacent to the tandem-repeat RUNX2 binding sites within the Col10a1 enhancer as previously described.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…This study proved that COL10A1 is a direct target of RUNX2 during chondrogenesis and has multiple RUNX2 binding sites within the proximal promoters of humans, mice, and chicks. Since COL10A1 is a specific marker of chondrocyte hypertrophy 13 , 14 it has been shown that the regulation of COL10A1 expression by RUNX2 is a key regulatory axis of chondrocyte hypertrophy. Although the importance of RUNX2 in chondrocyte hypertrophy has been elucidated, studies on the regulation of RUNX2 activity during chondrocyte hypertrophy are lacking.…”
Section: Introductionmentioning
confidence: 99%